Remittance Investment Climate Analysis in Rural Hometowns (RICART): Piloting a Tool on Rural Hometown Investing by Overseas Migrants - Ang, Alvin P (Archīum Ateneo, 2016)
This material contains findings of a pilot research tool --called the Remittance Investment Climate Analysis in Rural Hometowns (RICART)-- that sought to determine if rural hometowns of overseas migrants from the Philippines will invest in their birthplaces or not. The RICART project was courtesy of a research prize from the Global Development Network (GDN), with supplementary support from an anonymous Catholic donor from Europe. Two rural municipalities in the Philippines were studied here.